Analysis of the breathing function in wind instrumental musicians - Italo Paranhos Santos; Renato Fleury Cardoso; Franciele Angelo de Deus; Henrique Silveira Costa; Vanessa Pereira Lima (Hospital de Clínicas de Itajubá, 2023)
Objective: To conduct an integrative review of lung function and respiratory muscle strength in wind instrument musicians. The relationship between respiratory function and the use of wind musical instruments is an area of knowledge that has not been extensively explored. Methods: A bibliographic review was carried out in the MEDLINE, Embase, Cochrane, PeDro, BVS, Scopus, Web of Science, and SciELO databases by combining the keywords "respiratory function test", "wind instrument", musician, "pulmonary ventilation" and "Lung Function Test". Results: Initially, 108 articles were found, of which 11 were selected, totaling 596 wind instrumentalists who were part of the study groups. In most studies, musicians showed lower values of expired volume in one second (FEV1) and forced vital capacity (FVC) in spirometry than in the control group. However, there was no difference regarding the FEV1/FVC ratio, just as there was no difference in respiratory muscle strength or relationship with respiratory diseases. Conclusion: Current studies regarding the effect of wind instruments on individuals are unable to show positive or negative impacts on the respiratory health of this population.